Crop and Livestock Labor Standards by Size of Operation - Langemeier, Larry N. (My University, 1995)
Publication contains crop and labor standards developed to provide labor information for use in whole-farm and enterprise budgeting, forward planning, and comparative studies.
MF802_1995_10
Keywords: MF802; Economics; MF